Analysis of Anomalous Enhancement in TEC and Electron Density in the China Region Prior to the 17 March 2015 Geomagnetic Storm Based on Ground and Space Observations - Xiaoyun CHENG, Dongjie YUE, Changzhi ZHAI, Yutian CHEN, Xunzhe YIN (Journal of Geodesy and Geoinformation Science, 2023)
Total Electron Content (TEC) and electron density enhancement were observed on the day before 17 March 2015 great storm in the China Region. Observations from ground- and space-based instruments are used to investigate the temporal and spatial evolution of the pre-storm enhancement. TEC enhancement was observed from 24°N to 30°N after 10:00 UT at 105°E, 110°E and 115°E longitudes on March 16. The maximum magnitude of TEC enhancement was more than 10 TECU and the maximal relative TEC enhancement exceeded 30%. Compared with geomagnetic quiet days, the electron density of Equatorial Ionization Anomaly (EIA) northern peak from Swarm A/C satellites on March 16 was larger and at higher latitudes. NmF2 enhanced during 11:30—21:00 UT at Shaoyang Station and increased by 200% at ~16:00 UT. However, TEC and electron density enhancement were not accompanied by a significant change of hmF2. Most research has excluded some potential mechanisms as the main driving factors for storm-time density enhancements by establishing observational constraints. In this paper, we observed pre-storm enhancement in electron density at different altitudes and Equatorial Electrojet (EEJ) strength results derived from ground magnetometers observations suggest an enhanced eastward electric field from the E region probably played a significant role in this event.